The Cell Biology of Stem Cells - Meshorer, Eran.; Plath, Kathrin; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
The Cell Biology of Stem Cells discusses multiple aspects of stem cell biology, ranging from their basic molecular characteristics to the in vivo stem cell trafficking of adult stem cells and the adult stem-cell niche, and ends with a visit to regeneration and cell fate reprogramming. It provides much of the current understanding of the cell biology of stem cells and discusses many of the open questions that remain to be answered.
Early Embryonic Cell Fate Decisions in the Mouse -- Nuclear Architecture in Stem Cells -- Epigenetic Regulation of Pluripotency -- Autosomal Lyonization of Replication Domains During Early Mammalian Development -- Preservation of Genomic Integrity in Mouse Embryonic Stem Cells -- Transcriptional Regulation in Embryonic Stem Cells -- Alternative Splicing in Stem Cell Self-Renewal and Diferentiation -- MicroRNA Regulation of Embryonic Stem Cell Self-Renewal and Differentiation -- Telomeres And Telomerase in Adult Stem Cells and Pluripotent Embryonic Stem Cells -- X Chromosome Inactivation and Embryonic Stem Cells -- Adult Stem Cels and Their Niches -- Adult Stem Cel Diferentiation and Trafficking And Their Implications in Disease -- Vertebrates That Regenerate As Models For Guiding Stem Cels -- Reprogramming of Somatic Cells to Pluripotency.
Keywords: Life sciences; Cytology; Stem cells; Life Sciences; Stem Cells; Cell Biology